1972
DOI: 10.1136/pgmj.48.556.69
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of uncomplicated urinary tract infection in non-pregnant women

Abstract: SummaryA study of placebo treatment of acute symptomatic urinary tract infection in non-pregnant women showed that about 80%4 obtained sterile urine spontaneously within 5 months. About one-half of these had recurrent infection within a year.Antimicrobials produced a high immediate cure rate, but only 45°o maintained sterile urine for 2 years. The recurrence rate was highest during the first 2 months after treatment, and thereafter nearly constant during the subsequent 20 months. Twentynine percent of recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(59 citation statements)
references
References 11 publications
1
57
0
1
Order By: Relevance
“…women experience only single or sporadic infections, -20% suffer very frequent (three or more per year) recurrences ( 1). The apparent increased susceptibility to UTI in these patients cannot be explained by underlying functional or anatomic abnormalities of the urinary tract, but instead appears to arise from the interaction of infecting Escherichia coli strains with these patients' epithelial cells.…”
mentioning
confidence: 99%
“…women experience only single or sporadic infections, -20% suffer very frequent (three or more per year) recurrences ( 1). The apparent increased susceptibility to UTI in these patients cannot be explained by underlying functional or anatomic abnormalities of the urinary tract, but instead appears to arise from the interaction of infecting Escherichia coli strains with these patients' epithelial cells.…”
mentioning
confidence: 99%
“…Almost 27% of women developed a recurrent UTI within the 6 months (Foxman 1990) and nearly 50% of women developed a recurrence within the first year following the initial infection (Mabeck 1972). Clinical studies showed that only a fraction of r-UTI patients had obvious functional, anatomic and behavioral risk factors, which were considered to be strongly associated with an increased risk of r-UTI.…”
mentioning
confidence: 99%
“…When the uropathogen is sensitive to the chosen agent, oral antibiotics typically produce a rapid improvement in symptoms and sterilization of the urine (15, 16). Despite appropriate treatment of a primary UTI, 25 to 40% of adult women will have at least one recurrence (rUTI) within 6 months of her initial infection (33,45). Additionally, up to 20% of women may experience the symptoms of cystitis, or infection of the bladder, with accompanying urine cultures from clean-catch specimens below the diagnostic cutoff of Ͻ10 5 CFU/ml (13).…”
mentioning
confidence: 99%